Análisis de las precipitaciones en Colombia, pronóstico y tendencias (2021)
The objective of this document is to build downscaling models through the regression of principal components and thus be able to carry out a simulation of precipitation in Colombia during a period from 1981 - 2011 and to carry out climate projections in a period between 2011 - 2070., with the application of the previous SD statistical scale.